PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KINERJA KARYAWAN PT. BUMI PERSADA KARYA GRESIK - Nuraini Eka Pratiwi; Mochamad Syaiful Arif (Jurnal Ekonomi, Bisnis dan Social, 2024)
This research aims to: (1) To know the description of Communication, Work Environment and Employee Performance Productivity at PT. Bumi Persada Karya Gresik, (2) To determine the effect of Communication on Employee Performance Productivity at PT. Bumi Persada Karya Gresik, (3) To determine the effect of the Work Environment on Employee Performance Productivity at PT. Bumi Persada Karya Gresik, (4) To determine the effect of Communication and Work Environment on Employee Performance Productivity at PT. Bumi Persada Karya Gresik. The sampling technique in this study is Non Probability Sampling / Saturated Sampling, by distributing questionnaires or lists of statements to 40 respondents. Employee Performance Productivity, and also the Environment has a significant and positive effect on Employee Performance.